2000
DOI: 10.4049/jimmunol.164.2.1086
|View full text |Cite
|
Sign up to set email alerts
|

Soluble IL-4 Receptor Inhibits Airway Inflammation Following Allergen Challenge in a Mouse Model of Asthma

Abstract: In vitro and in vivo studies, in both animal models and human asthmatics, have implicated IL-4 as an important inflammatory mediator in asthma. In a murine asthma model, we examined the anti-inflammatory activities of soluble IL-4R (sIL-4R). In this model, mice sensitized to OVA by i.p. and intranasal (i.n.) routes are challenged with the allergen by i.n. administration. The OVA challenge elicits an eosinophil infiltration into the lungs, with widespread mucus occlusion of the airways, and results in bronchial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
96
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(100 citation statements)
references
References 54 publications
2
96
0
2
Order By: Relevance
“…not airway hyperresponsiveness, whereas anti-monocyte chemoattractant protein-1/CCL2 mAbs failed to suppress eosinophilic inflammation, but abrogated airway hyperresponsiveness (48). Interestingly, treatment with soluble IL-4R, as performed with these antagonists before OVA challenge in OVA-immunized mice inhibits mucus hypersecretion and eosinophil influx into the lungs, but not bronchohyperactivity to methacholine following allergen challenge (49). These findings strengthen the concept that blocking migration or activation of Th2 T lymphocytes prevents the successive events, which contribute to the pathogenesis of asthma.…”
Section: Discussionsupporting
confidence: 74%
“…not airway hyperresponsiveness, whereas anti-monocyte chemoattractant protein-1/CCL2 mAbs failed to suppress eosinophilic inflammation, but abrogated airway hyperresponsiveness (48). Interestingly, treatment with soluble IL-4R, as performed with these antagonists before OVA challenge in OVA-immunized mice inhibits mucus hypersecretion and eosinophil influx into the lungs, but not bronchohyperactivity to methacholine following allergen challenge (49). These findings strengthen the concept that blocking migration or activation of Th2 T lymphocytes prevents the successive events, which contribute to the pathogenesis of asthma.…”
Section: Discussionsupporting
confidence: 74%
“…4). Judging from these results and the fact that soluble IL-4R␣ administration inhibited Th2-induced eosinophilia, both IL-5 and IL-13 might be involved in airway eosinophilia coupled with eotaxin (21,22). In contrast to Th2, the role of Th1 cells in airway inflammation remains unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Several in vitro and in vivo studies have demonstrated that the sIL-4R binds IL-4 with high affinity and can function as an antagonist of IL-4 activity, competing with the mIL-4R on target cells for the binding of IL-4 (20,26,27,29,52). The production of sIL-4Ra is reduced in Il21r 2/2 mice, in accordance with reduced membrane-bound IL-4Ra and reduced IL-4 production.…”
Section: Discussionmentioning
confidence: 99%
“…Proteolytic cleavage releases sIL-4R, containing the extracellular portion of IL-4R, from the transmembrane and intracellular domains that remain cellbound. sIL-4R inhibits the biologic actions of IL-4 in vitro (28) and in vivo (29,52). sIL-4R detected in serum by ELISA on day 10 following immunization with NP-OVA in alum showed a significant decrease in sIL-4R in Il21r 2/2 mice when compared with WT mice (Fig.…”
Section: Decreased Soluble Il-4ra Correlates With Increased Ige In Seramentioning
confidence: 99%
See 1 more Smart Citation